The Significance of the Actions of the Hypocrites Towards The Messenger In The Holy Quran Present Tense As A Model - Ali , Intisar; Ismail, Mona (Islamic Sciences Journal, 2023)
This study is set to be focused on semantics as one of the pillars of linguistics, yet. It is an attempt to uncover the connotations expressed in actions of the hepocrapts against the prophet, Mohammed… ((may allah be pray upon him)). That are mentioned in the holy Quran . the present tense of verbs is chosen as a typical verb ,due to the indications of the tense on reocurrance and renewal aspects, so as to study those verbs to confirm by which how far did the hepocrapts go in their way in terms of hypocrisy over their actions .This research is based on an introduction along with two questions .First: to define semantics, verb and hypocrisy each in terms of language and terminology .The Second to draw analysis on the holy verses under study. Then a conclusion is drawn in terms of the significant results listed in the verses table line and included in the verbs relevant to the subject of the research .This research is taken from a master thesis made on the indications characterized in the actions of the hepocrapts in the holy Quran.